2021
DOI: 10.1186/s12909-021-03036-5
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Musculoskeletal Module using dissection videos: feedback from medical students

Abstract: Background and Aims Over the last two decades many medical schools have been exploring alternatives to hands-on cadaver dissection in teaching anatomy. This study aimed at reporting medical students’ feedback on using dissection videos in teaching anatomy of the musculoskeletal system. Methods Dissection videos were used to teach the anatomy of the musculoskeletal system for third year medical students. At the end of the module, feedbacks from medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
(35 reference statements)
1
14
0
1
Order By: Relevance
“…Students also mentioned increased motivation as an advantage of this strategy in the open-ended question. Similarly, in previous studies, motivation and satisfaction have been reported with peer teaching (Agius et al, 2018;Salomäki et al, 2014) and video dissection (DiLullo et al, 2006;Granger, 2004;Mustafa et al, 2021;Topping, 2014).…”
Section: Students 'Usage N (%) Categorysupporting
confidence: 69%
“…Students also mentioned increased motivation as an advantage of this strategy in the open-ended question. Similarly, in previous studies, motivation and satisfaction have been reported with peer teaching (Agius et al, 2018;Salomäki et al, 2014) and video dissection (DiLullo et al, 2006;Granger, 2004;Mustafa et al, 2021;Topping, 2014).…”
Section: Students 'Usage N (%) Categorysupporting
confidence: 69%
“…In addition, several studies have confirmed that PEOU of technology is an important predictor of PU and is interlinked to influence individual technology acceptance ( Choi et al, 2021 ; Hong X. M. et al, 2021 ). For teacher education students, social media such as short videos are more resourceful, interactive, and timely ( Mustafa et al, 2021 ), making it easier for them to access appropriate learning resources from short video platforms, and they are also more willing to use short video resources in collaborative learning ( Moreno-Guerrero et al, 2020 ), thus laying the foundation for being lifelong learners in their future work. They are therefore better prepared to become lifelong learners in their future educational endeavors.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, students’ self-efficacy is related to the PU and PEOU of technology ( Pan, 2020 ), through which learners can feel that technology is more useful and easier to use ( Nur and Joviando, 2021 ). As an important form of social media, short videos are more visible, more interactive, and richer resources to facilitate students’ learning ( Mustafa et al, 2021 ). Since teacher education students’ need more collaborative learning to achieve common learning goals in the learning process, if they can learn through the application of short videos in the collaborative learning process, it will not only improve their CS-E, but also be more beneficial for them to complete the corresponding collaborative learning and inquiry tasks ( Zheng et al, 2020 ).…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They act as a precursor to active learning within the classroom [ 12 ] or laboratory environment [ 13–15 ], as an additional means of consolidating prior learning [ 16 ], a supplement to taught material [ 17 ], and a means of personalising assessment and feedback [ 18 , 19 ]. A recent study by Mustafa et al (2021), investigating the use of videos to teach anatomical dissections, highlighted students favour a blended approach and would not want videos to replace face-to-face instruction [ 20 ]. The potential of blended learning as a flexible, accessible, and digitally enabled model has created a wave of activity amongst higher education institutions (HEIs), resulting in a broad range of practices.…”
Section: Video As a Learning Toolmentioning
confidence: 99%